Utilization of tree legume forages as protein sources of beef cattle ration - Manurung, Tambak (Indonesian Journal of Animal and Veterinary Sciences, 1995)
A study was conducted in Balai Penelitian Temak Bogor, for evaluating the use of tree legume as the main source of protein for growing cattle . The study was conducted for 17 weeks using 15 Ongole-crossed bull calves with body weight 77-138 kg . The study was carried out in randomized block design with 5 treatments and 3 replications . Five dietary treatments consist of lamtoro, glirisidia, caliandra, beefkwik and urea with 1496 crude protein and 6396 total digestible nutrient (TDN). Parameters measured were feed consumption, nutrients digestibility, nitrogen retention, weight gain and feed and protein efficiency . The results showed that the tree legume rations had higher (P<0.01) dry matter, organic matter, crude protein and TDN consumption than the beefkwik and urea, but the nutrient digestibilities were lower especially for caliandra (P<0.01) . Caliandra also had lower nitrogen retention than the others . Average daily gain of cattle fed with lamtoro and glirisidia were higher (P<0.01) than that of caliandra, but between lamtoro and glirisidia didnt show the significant different . Caliandra and beefkwik produced different average body weight gain (P<0.01) . Beefkwik produced higher feed and protein efficiency than tree legume ration especially as compared with caliandra (P<0 .01) but among tree legumes, glirisidia produced higher feed and protein efficiency than the caliandra (P<0.01) . It is concluded that glirisidia was the best forage as protein source for growing calves. Key words : Tree legume, protein, beef cattle